Assessment of hearing and vision impairment in cohort studies collecting cognitive data in older adults. Issue 11 (1st February 2022) - Liu, Chelsea; Nagarajan, Niranjani; Assi, Lama; Jiang, Kening; Powell, Danielle S.; Pedersen, Emily; Rosman, Lori; Villavisanis, Dillan; Carlson, Michelle C.; Swenor, Bonnielin K.; Deal, Jennifer A.
Abstract: Introduction: There are no standard practices for considering sensory impairment in studies measuring cognitive function among older adults. Exclusion of participants with impairments may inaccurately estimate the prevalence of cognitive impairment and dementia. Methods: We surveyed prospective cohort studies measuring cognitive function in older adults, determined the proportion that excluded participants based on sensory impairment and the proportion that assessed each type of sensory impairment, and described the methods of sensory assessment. Results: Investigators/staff from 85 (of 192 cohorts) responded; 6 (7%) excluded participants with severe impairment; 80 (94%) measured hearing and/or vision impairment, while 5 (6%) measured neither. Thirty‐two (38%) cohorts assessed hearing objectively and 45 (53%) assessed vision objectively. Discussion: Findings indicate variation in methods used to assess sensory impairment, with potential implications for resource allocation. To ensure equitable inclusion of study participants, consensus is needed on best practices standardized protocols for assessment and accommodations of sensory impairment.